(untitled) - Cooper, Simon (Oxford, 2007)
The Blackstone's Practical Policing Series covers a range of topical subjects of vital importance in today's policing arena. Each practical guide contains clear and detailed explanations of the relevant legislation, accompanied by practical scenarios, illustrative diagrams and useful checklists. Packed with a wealth of information, the Blackstone's Practical Policing Series ensures you have ready access to the tools you need to take on any policing challenge.
Keywords: Traffic regulations,Traffic violations,Motor vehicles; Law and legislation; Great Britain,Great Britain,Great Britain